Financial contagion analysis on asset return of S&P 500 Index, Shanghai Index, and Hang Seng Index with Jakarta Composite Index for the period 2017 – 2023 - Ferdy Fardian; Brady Rikumahu (Journal of Digital Business and Marketing, 2025)
Purpose: This study investigates financial contagion—the transmission of risk and instability between markets and using the co-volatility contagion test method developed by Fry-McKibbin (2018). This study aims to analyze the volatility linkages among major global stock markets and their impact on Indonesia’s market during economic crises. Research Methodology: This study examines daily asset returns from January 2017 to December 2023 for the S&P 500 Index (SPX, United States), Shanghai Composite Index (SCI, China), Hang Seng Index (HSI, Hong Kong), and Jakarta Composite Index (JCI, Indonesia). The co-volatility contagion framework measures changes in market correlations between crisis and non-crisis periods. Results: The findings reveal contagion from SPX, SCI, and HSI to the JCI, with varying co-volatility patterns. The SPX–JCI relationship shows significantly positive co-volatility differences that decline during crises, indicating synchronized but independent movements under global uncertainty. The SCI–JCI differences were significantly negative with low magnitudes, suggesting opposite movement tendencies during crises. HSI–JCI differences were also significantly negative, reflecting reduced connectivity and divergent responses to global risks. Conclusions: Distinct co-volatility patterns indicate different market sensitivities to global uncertainty, emphasizing the importance of tailored investment and policy strategies. Limitations: This study focuses on four markets and a defined time span, potentially limiting generalizability. However, it does not account for sector-specific contagion effects. Contribution: This study provides empirical evidence of volatility transmission mechanisms, offering valuable insights for investors, market participants, and policymakers to enhance risk assessment and investment strategies.